2021
DOI: 10.3389/fonc.2021.585257
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Real-Time Contrast-Enhanced Ultrasound in Guiding Radiofrequency Ablation of Reninoma: Case Report and Literature Review

Abstract: BackgroundReninoma is a rare renal endocrine tumor that can cause secondary hypertension, characterized by hypertension, hypokalemia, high renin and aldosterone with normal aldosterone renin ratio (ARR), and occurs more in young female. Mainstream treatment option is surgery, but is less suitable for small or deep lesions, which makes ablation a promising alternative.Case presentationTwo young female with typical manifestations of reninoma, including hypertension, hypokalemia, high renin, high aldosterone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Some studies have encouraged the use of CEUS during thermal ablation. 2,[5][6][7] Considering that microbubbles are the main components of ultrasound contrast agent, exploring the mutual influence of MWA and microbubbles is important and clinically valuable. In this study, our results indicated that although MBs (SonoVue) had no significant influence on MWA, MWA could induce the destruction of microbubbles in a temperature-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have encouraged the use of CEUS during thermal ablation. 2,[5][6][7] Considering that microbubbles are the main components of ultrasound contrast agent, exploring the mutual influence of MWA and microbubbles is important and clinically valuable. In this study, our results indicated that although MBs (SonoVue) had no significant influence on MWA, MWA could induce the destruction of microbubbles in a temperature-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Furthermore, some studies have encouraged the use of CEUS to monitor thermal ablation in real time. 2,[5][6][7] Therefore, microbubble injections could be a commonly performed during thermal ablation. However, the precise predicting and real-time monitoring requirements for the ablation range are becoming increasingly strict in clinic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, four tumors, with small size (1.0~1.5cm) and located completely in the cortex with no protrusion, were missed by ultrasound. Contrast enhanced ultrasound might be helpful [4,18]. Li et al reported two cases of JGCT, invisible by previous conventional ultrasound, found by contrast enhanced ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor is also called reninoma because it can secrete renin [1,2]. Since the rst report of JGCT in 1967 [3], fewer than 200 cases have been reported in the literature [4]. It is more common in young females aged 20-39 years, with a male: female ratio of 1:2 [5].…”
Section: Introductionmentioning
confidence: 99%